A PERAN PEMIMPIN DALAM MENINGKATKAN DISPLIN KERJA DAN PRODUKTIVITAS KERJA KARYAWAN - Komang Trisna Sari Dewi (ARTHA SATYA DHARMA, 2021)
Abstract. The purpose of this study was to determine the role of leadership and work discipline on productivity of employees of the Department of Education, Youth and Sports, Buleleng Regency. This study uses a quantitative approach. Data collection techniques were used in the form of a questionnaire. Where selected as respondents are all employees who work in the Department of Education, Youth and Sports, Buleleng Regency, 68 people with a t-table value for a significant level of = 0.05 and a degree of freedom (df) = 66 is 0.2 2012 All relationships examined in this study on average showed significant results related to Leadership on Work Discipline, Leadership Role on productivity, Role of Work Discipline on productivity, each with a tstatistic value > from t-table (19.058 > 0.22012) , (1.370 > 0,2012), (5.676 > 0,2012).